Decision Support System For Choosing Food Menus In Patients With Gout Using The Simple Additive Weighting (Saw) Method At Harapan Doa Hospital, Bengkulu City - Fadhilah, Abyyu; Supardi, Reno; Elfianty, Lena (Jurnal Komputer Indonesia, 2024)
A Decision Support System is generally defined as a system that is able to provide problem-solving skills and communication skills for semi-structured problems. This research uses the Simple Additive Weighting method made using a scope-based application, namely Visual Studio Code using MySql as the database. The data collection methods carried out in this study are observation, interviews and literature studies. The purpose of this study is to create a decision support system for choosing food menus for gout patients at Harapan Doa Hospital, Bengkulu City, so that in the selection of food menus researchers use the Simple Additive Weighting method with a computerized system. The SAW method is often known as the weighted addition method. The basic concept of the SAW (Simple Additive Weighting) method is to find the weighted sum of the performance ratings on each alternative on all attributes. Application of meto